PROBLEMS AND LAND OWNERSHIP STATUS IN FOREST AREAS AFTER THE ELIMINATION OF LAW NUMBER 6 OF 2023 CONCERNING JOB CREATION - ILHAMDI (Proceeding International Conference on Social Sciences, 2026)
This study analyzes how Law Number 6 of 2023 concerning Job Creation (the Job Creation Law) reconstructs the previously closed status of land ownership in forest areas and the new problems that have emerged since the enactment of the Job Creation Law. The research focuses on the regulation of land ownership in forest areas and the issues that have arisen since the enactment of the Job Creation Law, as well as land disputes within forest areas. Using a juridical-normative approach and analyzed through the lens of Progressive Legal Theory and Legal Certainty Theory, this study finds that the Job Creation Law represents a paradigm shift from a security-oriented approach (oriented toward security/restrictions) to an access-oriented approach (oriented toward access and utilization). The novelty of this research lies in identifying the "Legal Hybridity" created by the Job Creation Law, where it attempts to reconcile the logic of conservation (forestry law) with the logic of investment and agrarian justice (agrarian law) within a single regulatory framework, which in turn creates new tensions in legal interpretation at the implementation level.